From the novísimos to Félix F. Casanova: union of life and oeuvre, counterculture and rock music - Nicolás Díez, Sofía (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
In this article, I consider the writer Félix F. Casanova to demonstrate characteristics of poetry written durin late Francoism and trasition to democracy. First, his case demonstrates the fusion of poets' live and oeuvres. Second, it demonstrates the influence of counterculture on poetry from the time period. Most importantly, however, the relationship of poetry with rock music of which I consider his case to outline a brief archaeology of recovery due to the critical absence on this aspect. These three elements will be intimately related in underground authors and therefore absent form the literary field during spanish transicion, as is the case with Casanova, and interpreted under paradigm that deactivates it, as is the case with novisimo authors. I question the critical construct and review the first signs of rock in Casanova's poetry without forgetting the movement precedents. These can be appreciated from textual, cultural and socioliterary perspectives.
Keywords: late francoism; spanish transition; poetry; counterculture; rock; life-work